The WISDOM radar on board the ExoMars 2022 Rover: Characterization and calibration of the flight model. (15th September 2020) - Hervé, Y.; Ciarletti, V.; Le Gall, A.; Corbel, C.; Hassen-Khodja, R.; Benedix, W.S.; Plettemeier, D.; Humeau, O.; Vieau, A.J.; Lustrement, B.; Abbaki, S.; Bertran, E.; et al.
Abstract: The ground penetrating radar WISDOM on board the Rover of the ExoMars 2022 mission (ESA/Roscosmos) will be a pioneer in the exploration of the Martian subsurface from the surface (until now, Martian sounding radars have been operated from orbit). WISDOM will image the first meters below the surface of Oxia Planum — the ExoMars 2022 landing site — with the objectives of revealing its geological history and identifying safe and promising scientific targets for subsurface sampling by the Rover drill. In this paper, we present the qualification, characterization and calibration tests that have been conducted on WISDOM flight model in order to assess its performance, build the data processing pipeline and prepare scientific return of this experiment. In most favorable but geologically plausible cases (low loss and homogeneous subsurface, smooth interface), WISDOM can detect a buried interface down to a depth of 8 ​m with a vertical resolution of 3 ​cm (for a subsurface dielectric constant of 4). Its penetration depth is typically 2 ​m in less favorable environments. For safety reason, WISDOM antennas are accommodated 38 ​cm above the ground; the amplitude of the surface echo will be used to estimate the top layer dielectric constant with an accuracy of 13% which translates into an accuracy of 6% on the distance/depth assessment. WISDOM data processing chain includes corrections aiming at removing parasitic signals of various origins (electronic coupling, antenna crosstalk, multiple surface echoes, etc.) and at correcting the data to a reference temperature and antenna elevation; it has been designed to automatically produce calibrated radargrams in less than 20 ​min as required for the mission operations. Additional more sophisticated processing will be manually run in parallel. The impact of the Rover structure on measurements has been investigated and can be partially removed. Highlights: The WISDOM radar of the ExoMars mission will investigate the Martian subsurface. Qualification, characterization, calibration tests of the flight model are described. The pipeline used to produce calibrated data that will be archived is presented.